Analysis of Strategies, Methods, and Tools in Detecting Fraud after Covid 19 Pandemic - Natalis Christian; Fiona Vinelia; Juwenni Juwenni; Michael Learns Tay; Meliesa Chandrawati (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to analyze and compare the strategies, methods and tools used by various institutions in the world and different countries in detecting fraud. Currently, Fraud has become a common thing in the world of economics and business. As one of the preventive measures, robust detection is required. Methods and ways of detecting fraud are constantly changing and improving. Where every country certainly has a strategy in dealing with fraud cases to protect the country's economy. Without an appropriate strategy, it will facilitate further crime. This research will also explain fraud detection methods that have been applied by various institutions. The data before and after the Covid period did not show a very significant difference, so it can be concluded that whether external influences from outside the company did not significantly influence the occurrence of fraud in the company. Therefore, if we do not aware about the strategies, methods, and tools for detecting cases of fraud in companies, we will never know whether the company is in good condition or not.